Immune Checkpoint Inhibitors Plus an Anti-VEGF Antibody as the First-Line Treatment for Unresectable Hepatocellular Carcinoma: A Network Meta-Analysis and Cost-Effectiveness Analysis - Li, Lu; Yang, Shilei; Chen, Yanwei; Tian, Li; He, Ying; Wu, Bin; Dong, Deshi (Frontiers in Pharmacology, 2022)
Background: Sintilimab + a bevacizumab biosimilar (IBI305) (SB) and atezolizumab + bevacizumab (AB) are approved for treating unresectable hepatocellular carcinoma (HCC). Oncologists and patients are indeterminate which treatment is more preferable, assessing a network meta-analysis and cost-effectiveness comparison between them is needful. Objective: To evaluate the cost-effectiveness of SB and AB compared with sorafenib in treating unresectable HCC. Materials and Methods: Data used in our analysis were from patients in the ORIENT-32 and the IMbrave150 phase III randomized clinical trials. A Bayesian network meta-analysis and cost-effectiveness analysis that included 1072 patients were implemented in this study. A partitioned survival model was applied to patients with unresectable HCC. The model was designed as a fifteen-year time horizon, a one-month cycle, and a 5% discount rate for costs and outcomes. In China, an incremental cost-effectiveness ratio (ICER) value of less than $33,500 (3 times GDP per capita in 2020) per quality-adjusted life-year (QALY) is considered cost-effective. The influence of parameter uncertainty on the results was verified by one-way deterministic sensitivity analysis and probability sensitivity analysis; the patient assistant program (PAP) was also conducted in the scenario analyses to explore the associations of the cost of SB and AB with cost-effectiveness. Results: For the model of 1072 patients, the treatment of SB produced an additional 0.617 QALYs compared with sorafenib, resulting in an ICER of $39,766.86/QALY, and the treatment of AB produced an additional 0.596 QALYs compared with sorafenib, resulting in an ICER of $103,037.66/QALY. Probability sensitivity analysis shows when the willingness-to-pay (WTP) threshold was $33,500/QALY, the cost-effectiveness possibility of SB and AB were 15.4% and 0.4%, respectively. In the scenario analyses, the probability of SB and AB regimens being cost-effective were 65.4% and 15.8% at the WTP of $33,500/QALY, respectively. Conclusion: The findings from our study showed that sintilimab + a bevacizumab biosimilar is a cost-effective regimen compared with sorafenib for the first-line therapy of unresectable HCC in China at a $33,500 WTP threshold if the sintilimab PAP was considered. However, the atezolizumab + bevacizumab regimen isn't a cost-effective treatment whether the atezolizumab PAP was considered or not.